Geographical perspectives: regional development and transnational learning - Virkkala, Seija (Routledge, 2013)
This chapter discusses the relationship between regional development and transnational learning. Transnational learning is seen as a resource for regional development, and this chapter examines how it can boost regional development, and under what preconditions. It deals with local communities and sub-national units, the main emphasis being on the latter. The concepts of region, regional and local development, regional development network and transnational learning network, path dependency, absorptive and development capacities of regional actors, and development policies are explored. With reference to Chapter 1, this chapter combines the structural view, according to which regions are products of broader structures, with the idea of regions as voluntarily constructed entities involving individual actors. It also discusses the territorial and relational approaches to regional and local development. Within the territorial approach, the region is considered the starting point for analysis, and local and regional processes, carried out through institutions and agents, are the key driving forces. The point of departure with the relational approach is the idea of regions as entities that are governed by forever changing flows and networks, instead of considering regions as static units. The territorial approach is useful when discussing regional development and learning, as well as the development policies of the regional development network. The relational approach, on the other hand, can be used in the analysis of emerging transnational learning networks. Regional and local development can be seen as a process of interplay between resources, networks and institutions. Development is path-dependent and based on learning, and there can be both positive and negative lock-ins in a regional development path. This chapter discusses how regional actors can escape negative lockins and external crises with the help of transnational learning. Transnational learning can lead to the discovery of new directions and the creation of new emerging regional structures, for instance through new practices employed by regional actors. The chapter also examines the preconditions for effective transnational learning, such as regional strategies, as well as reflexive regional actors who draw upon structures with absorptive and development capacities. It also considers how these absorptive and development capacities can be improved through transnational inputs enabling a learning spiral. In this chapter, learning is seen as a process of knowledge creation and conversion. Knowledge types, including ‘know-how’, ‘know-what’, ‘know-why’ and ‘know-who’, introduced by Lundvall and Johnson, are applied in a regional context, especially in regional and local development and development policies. The SECI model, proposed by Nonaka and Takeuchi and introduced by Mariussen in Chapter 1 of this volume, will be used in this chapter for analyzing transnational learning inputs in regional development strategies and practices, the preconditions for the creation of development paths, and the absorptive and developmental capacities of regional actors. By reflecting on, externalizing and translating good practices from other regions, combining them with existing elements and internalizing the resulting new practice, the absorptive and development capacities of regional actors increase and a cumulative knowledge spiral, important especially for peripheral regions, can be initiated. The chapter suggests a broad typology of regions apt for transnational learning based on different innovation modes.
Keywords: regional development; networks (societal phenomena); regional economy; regionalism; innovations; enterprises; economic development; learning; regionality; cooperation (general); fi=Aluetiede|en=Regional Studies|